The Capillary Index Score before thrombectomy: an angiographic correlate of favorable outcome. (12th November 2015) - Labeyrie, Paul-Emile; Redjem, Hocine; Blanc, Raphaël; Labeyrie, Marc-Antoine; Bartolini, Bruno; Ciccio, Gabriele; Robert, Thomas; Gilboa, Boaz; Fahed, Robert; Abrivard, Marie; Piotin, Michel
Abstract : Background and purpose: The angiography based Capillary Index Score (CIS) has recently emerged as a potential surrogate marker of cerebral perfusion before intra-arterial thrombolysis. We assessed the prevalence of a favorable CIS (f-CIS) and its relationship with clinical outcome in patients treated by mechanical thrombectomy (MT). Methods: Data from consecutive patients treated by MT from acute middle cerebral artery (MCA) occlusion were retrospectively analyzed. CIS was calculated from a pre-intervention cerebral angiogram. Association with favorable clinical outcome (modified Rankin Scale score ≤2) at 3 months was assessed in multivariate analysis. Results: 146 patients were included in the study. f-CIS was observed in 106/146 (72%) patients with an acceptable inter-rater agreement (κ=0.73, p<0.001). It was associated with a lower pretreatment National Institutes of Health Stroke Scale (NIHSS) score (p=0.014), an isolated M1/M2 occlusion without internal carotid occlusion (p=0.042), and an Alberta Stroke Program Early CT Score (ASPECTS) >4 (p=0.004). In binary regression, a favorable outcome was independently associated with f-CIS (OR (−95% CI, +95% CI)=3.8 (1.3 to 10.9), p=0.013), as well as NIHSS (p=0.007), ASPECTS (p=0.005), isolated M1/M2 occlusion (p=0.013), and age (p=0.032). The positive predictive value of f-CIS for a favorable outcome was 67%. Conclusions: f-CIS was strongly associated with a favorable outcome after MT of acute MCA occlusion. As an easy surrogate marker of cerebral perfusion, it may be a useful—albeit not sufficient—diagnostic test to select patients just before an MT or to manage them after recanalization.